Plasma synthesis of nanodiamonds in ethanol - Nee, Chen Hon (Elsevier, 2019)
In this work, we examined the characteristics of the plasma formed by fs laser filamentation in ethanol that affected the nanodiamonds formation by optical emission spectroscopy. Molecular and atomic C species were detected in the plasma as the precursors to the nanodiamonds formed; above the threshold laser energy of 360 μJ. Thus, the generation of homogeneous nanodiamonds was identified to be occurred within laser energy of 360–550 μJ where atomic C, ionized C and C2 clusters coexisted. The process of fs laser filamentation is monitored with in-situ absorbance measurement of ethanol. The intensity of the absorbance peak of the sample at ∼228 nm, corresponds to intrinsic absorbance of diamond (σ→ σ* transition) was observed to increase with irradiation time. The prepared samples are characterized by using Raman spectroscopy, XPS and TEM. Nanodiamonds of <5 nm in size were produced. Photoluminescence measurements show that the sample fluoresce at ∼490 nm, when excited by 266 nm, 355 nm, 368 nm and 406 nm laser while additional photoluminescence peak is detected at 329 nm when excited by 266 nm laser.